A TECTONO-MAGMATIC CORRELATION OF BASALTIC ROCKS FROM OPHIOLITE MÉLANGES AT THE NORTH-EASTERN TIP OF THE SAVA-VARDAR SUTURE ZONE; NORTHERN CROATIA; CONSTRAINED BY GEOCHEMISTRY AND PETROLOGY - Slovenec, Damir; Lugović, Boško; Meyer, Hans-Peter; Šiftar, Gordana Garapić (Ofioliti, 2011)
Ophiolite mélanges of Mts. Kalnik and Ivanšcica form the northern sector of the Kalnik Unit and represent the northeasternmost exposed tip of the Sava- Vardar Suture Zone. Petrological; geochemical and isotopic characteristics of extrusive rock blocks incorporated in the mélanges; particularly of pillow basalt altered to spilite; in association with radiolarian cherts; allow the rocks to be separated into five distinct groups. Each group has an age-marker based on the radiolarian assemblage in the associated cherts and/or on isotope dating which; along with previously published data on the Kalnik Unit; provide detailed analysis of the approximately 80 Ma long geodynamic evolution of the Repno Oceanic Domain - a part of the Meliata-Maliak ocean system. The rock groups are: (1) Late Anisian alkali basalts [(La/Lu)cn = 5.9-7.2; eNd(T) = +2.96; Cpx-TiO2 = 3-6wt%] related to a terminal phase of intracontinental rifting; (2) enriched E-MORB-type basalts [(La/Lu)cn = 2.4-2.8; eNd(T) = +4.74; Cpx-TiO2 = 2.1-2.9wt%] and depleted E-MORB-type basalts [(La/Lu)cn ~ 1.5; eNd(T) = +5.26; Cpx- TiO2 = 1.9-2.3wt%] which reflect successive proto-oceanic crust formed at the ridge during the early Ladinian and late Ladinian; respectively; (3) middle Carnian T-MORB-type basalts [(La/Sm)cn = 0.79-0.87; eNd(T) = +6.63; Cpx-TiO2 = 1.2-2.2wt%]; representing crust from an evolved spreading center; (4) NMORB- type basalts [(La/Sm)cn = 0.67-0.87; eNd(T) = +6.58; Cpx-TiO2 = 0.6-1.9wt%] with inherited supra-subduction signature that diminish from the Late Carnian basalts [(Nb/La)n = 0.81] to the Bajocian basalts [(Nb/La)n = 1.1]; and Middle Jurassic (Bathonian?) N-MORB-type basalts with recurrent subduction related influence [Nb/La)n = 0.72; (La/Sm)cn = 0.76; eNd(T) = +6.23]; (5) late Bathonian medium-Ti [(Nb/La)n = 0.24-0.72; eNd(T) = +6.30; Cpx-TiO2 = 0.6- 1.1wt%] to late Oxfordian low-Ti IAT-type basalts [(Nb/La)n = 0.12-0.22; eNd(T) = +6.31; Cpx-TiO2 = 0.2-0.6wt%] which reflect melts derived from a metasomatized and successively depleted mantle wedge in an extensional proto-arc setting.